Analisis Laporan Keuangan dengan Menggunakan Metode RGEC pada Perusahaan Perbankan Konvensional - Viegas, Mario; Ratih, Suklimah (Jurnal Syntax Fusion, 2021)
In choosing a banking company to use the producers and services of the banking company. It is important to note that the selection of a bank is not only based of the fame on the bank or the presence of acquaintances or family members who work in the company. However, the selection of a good and correct bank is to look at the soundness of the bank. Therefore, this study aims to determine the soundness of conventional banking companies listed on the Indonesia stock exchange in 2016 - 2019. The method used in sampling is purposive sampling, especially for banks that are included in book 4 so that researchers get 6 banking companies that in accordance with the criteria in 2016 - 2019. The research technique used by the researcher is to calculate the ratio based on the RGEC method. The result of this study indicates that 3 out of 6 conventional banks have a very healthy level of health and the other 3 banks have a healthy level of health.